PATTERN OF ADMINISTRATIVE GOVERNANCE IN KAARUYAN VILLAGE OFFICE, MANANGGU DISTRICT BOALEMO DISTRICT - indriani frianka tumewu; djamila podungge; fibriyanti lakoro (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The purpose of this study was to determine and describe the pattern of administrative governance in the Kaaruyan Village Office, Mananggu District, Boalemo Regency This research is a descriptive research type with a qualitative approach. This type of research is used because it is to find out the reasons for the effective administrative governance pattern in Kaaruyan village.The data sources used in qualitative research are primary data sources and secondary data sources. The data analysis techniques used are 1) Data Reduction; 2) Data Display (Data Presentation); 3) Conclusion The results of the research in the field conclude that the pattern of administrative governance goes through 5 stages, namely: 1) Transparency. The pattern of governance of transparency in Kaaruyan Village is carried out by making announcements on information boards, printing billboards of village budgets and posting them in front of the village office and informing all information to the community every time there is a meeting; 2) Accountability. The principle of accountability in the Kaaruyan Village is carried out with all reports on the implementation of village governance having been carried out through the Village Financial Accountability Report to the sub-district and district levels; 3) Responsibility. The pattern of responsibility in Kaaruyan Village in administrative governance with government regulations and applicable laws and regulations which is a reference in administrative governance and the efforts made are by designing minimum service standards at the village office in a professional and fair manner; 4) Independence. The pattern of independence in administrative governance is shown by the absence of intervention from political parties or other institutions outside Kaaruyan Village and from existing institutions, both institutions within the government and those outside Kaaruya Village; 5) Equality and fairness. The pattern of equality and fairness in administrative governance is carried out with every problem that occurs in the community, it must go through the village government and can be resolved fairly and wisely and every agreement made before the government must be in accordance with applicable regulations.